MAKNA UPACARA ADAT TRADISI BOLIMAU CONO SEBAGAI KEARIFAN LOKAL DI KECAMATAN UJUNGBATU KABUPATEN ROKAN HULU PROVINSI RIAU (Fenomenologi Alfred Schutz) - Bimantara, Rota; Salam, Noor Efni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
District Ujungbatu is one of the areas is found in the district Rokan Hulu , that their culture viscous with the malays , having tradition and habits and others .One for tradition owned is culture bolimau cono / habit is a tradition which has been handed down from one generation from generation to generation. Tradition bolimau cono viewed communities ujungbatu as tradition that which has significance , social aspects , values .This is done to coming to the tradition the holy month of Ramadhan by making traditional ceremonies earmarked for bersilahturahmi of the community .This study aims to to know meaning physical symbol , local what social aspects and values and it was due to in traditional ceremonies bolimau cono as the local wisdom in Kecamatan Ujungbatu Kabupaten Rokan Hulu. Calculation methods were used is qualitative with the approach phenomenology .The subject of writing this is an offender traditional ceremonies bolimau cono .Informants were selected in the sampling method of technique purposive sampling consisting of four people of adat figures or the community leader in ujungbatu namely Datuk Bendaharo , Datuk Paduko Sindo , Datuk Bimbo , and Datuk Ajo Tan Mudo .The writing of data obtained by deep through interviews , observation , documentation , the literature study and the tracing online .To test the validity of data using credibility test .As for data analysis technique by reduction of data , collect the data , provides the data , draw a conclusion and evaluationThe results of the study showed that tradition bolimau cono no meaning is considered as a ceremonial welcome the holy month of Ramadhan and just inherited from an ancestor , but also as a medium the decline in values set on high from the mamak to nephews / nieces , the meeting them and deal with them , having deliberation / potang sejodah social aspects , gotong royong and tourist destinations .Then had ethnic harmony values , simplicity , togetherness , social law , protect each other , the community economy , in patterns of thought, trend and value of religion.Keyword: Tradition, phenomenology.